2021
DOI: 10.1038/s41375-021-01441-9
|View full text |Cite
|
Sign up to set email alerts
|

A T cell inflammatory phenotype is associated with autoimmune toxicity of the PI3K inhibitor duvelisib in chronic lymphocytic leukemia

Abstract: Several PI3Kδ inhibitors are approved for the therapy of B cell malignancies, but their clinical use has been limited by unpredictable autoimmune toxicity. We have recently reported promising efficacy results treating chronic lymphocytic leukemia (CLL) patients with combination therapy with the PI3Kδγ inhibitor duvelisib and fludarabine cyclophosphamide rituximab (FCR) chemoimmunotherapy, but approximately one-third of patients develop autoimmune toxicity. We show here that duvelisib FCR treatment in an upfron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 21 publications
3
24
0
Order By: Relevance
“…In this study, we also find that patients with toxicity have evidence of an activated CD8 T‐cell population with Th17 differentiation at baseline that increases at the time of toxicity, and an associated increase in their CD8:Treg ratio. These data are similar to our recent findings among patients with CLL receiving duvelisib with fludarabine/cyclophosphamide/rituximab (FCR) in a front‐line setting 14 . This increasing body of work implicates not just alteration in Tregs but also baseline Th17 differentiation and increase in CD8 T cells during therapy among the causes of PI3K inhibitor‐induced toxicity.…”
Section: Figuresupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, we also find that patients with toxicity have evidence of an activated CD8 T‐cell population with Th17 differentiation at baseline that increases at the time of toxicity, and an associated increase in their CD8:Treg ratio. These data are similar to our recent findings among patients with CLL receiving duvelisib with fludarabine/cyclophosphamide/rituximab (FCR) in a front‐line setting 14 . This increasing body of work implicates not just alteration in Tregs but also baseline Th17 differentiation and increase in CD8 T cells during therapy among the causes of PI3K inhibitor‐induced toxicity.…”
Section: Figuresupporting
confidence: 89%
“…These data are similar to our recent findings among patients with CLL receiving duvelisib with fludarabine/cyclophosphamide/ rituximab (FCR) in a front-line setting. 14 This increasing body of work implicates not just alteration in Tregs but also baseline Th17 differentiation and increase in CD8 T cells during therapy among the causes of PI3K inhibitor-induced toxicity. Future work should focus on validation in larger cohorts as well as attempting to mitigate this toxicity by identifying plasma or cellular biomarkers for risk or a combination therapy partner that mitigates these T-cell effects.…”
Section: Discussionmentioning
confidence: 99%
“…Treg disruption by PI3K inhibitors has been associated with frequent and severe immune-mediated adverse events ( 67 , 129 ). A noteworthy study also found that low baseline Tregs in patients treated with duvelisib/FCR predicted immune-mediated toxicities ( 130 ). The authors observed that granzyme B+ Tregs were increased after duvelisib/FCR treatment in CLL patients and suggested that this phenotype indicated more activated and apoptotic Tregs ( 130 ).…”
Section: Impact Of Targeted Therapiesmentioning
confidence: 99%
“…A noteworthy study also found that low baseline Tregs in patients treated with duvelisib/FCR predicted immune-mediated toxicities ( 130 ). The authors observed that granzyme B+ Tregs were increased after duvelisib/FCR treatment in CLL patients and suggested that this phenotype indicated more activated and apoptotic Tregs ( 130 ). PI3K inhibitors are now being developed with strategies in mind to mitigate adverse events by limiting Treg-depleting effects ( 131 , 132 ).…”
Section: Impact Of Targeted Therapiesmentioning
confidence: 99%
“…Fatal adverse events were reported in 19 patients on the duvelisib and 7 patients on the ofatumumab arm [20]. Deregulation of Tregs accompanied by activation of Th17 cells was linked to autoimmune toxicity with idelalisib and duvelisib therapy [21,22 ▪▪ ], thus providing an explanation for significant overlap in toxicities between the two drugs.…”
Section: Phosphoinositide-3-kinase Inhibitors Approved In Therapy Of ...mentioning
confidence: 99%